Research progress on the application of machine learning in inflammatory skin diseases - GUO Jingxue; LIU Yongsheng; YANG Xueying; LI Jiaojiao; LI Dan; LI Yiqun; LI Yanfei; ZHANG Junjing (Pifu-xingbing zhenliaoxue zazhi)
In recent years, the application of artificial intelligence in the healthcare field has received widespread attention. Among them, machine learning technology has been extensively applied in various aspects of inflammatory skin diseases, including screening and diagnosis, management and monitoring, classification and evaluation, and treatment, providing new methodologies for precision medicine. This article reviews the predictive models, early diagnostic models, disease severity assessment models, differential diagnostic models, automated scoring models, prognostic evaluation models, and disease classification models of machine learning in inflammatory skin diseases, such as atopic dermatitis, acne, and psoriasis. It explores the advancements in machine learning for inflammatory skin diseases and provides new insights for precision treatment and prognosis evaluation.